2014
DOI: 10.1038/jcbfm.2014.6
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Mild Traumatic Brain Injury Results in Long-Term White-Matter Disruption

Abstract: Mild traumatic brain injury (mTBI) is an increasing public health concern as repetitive injuries can exacerbate existing neuropathology and result in increased neurologic deficits. In contrast to other models of repeated mTBI (rmTBI), our study focused on long-term white-matter abnormalities after bilateral mTBIs induced 7 days apart. A controlled cortical impact (CCI) was used to induce an initial mTBI to the right cortex of Single and rmTBI Sprague Dawley rats, followed by a second injury to the left cortex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
90
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 89 publications
(101 citation statements)
references
References 45 publications
(77 reference statements)
8
90
3
Order By: Relevance
“…Overall, we demonstrated that mTBI can lead to long-term alterations in WM microstructural integrity distal to the injury site at the AC in the developing brain, where repeated injury exacerbates abnormalities, similar to adult TBI [16]. Such increases in FA, in view of the significantly reduced RD and unaltered AD, clearly report WM microstructural disruption and suggest potential myelin-based dysregulation of microstructural integrity, as RD is often associated with myelin changes whereas AD is associated with axonal injuries [35, 64].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Overall, we demonstrated that mTBI can lead to long-term alterations in WM microstructural integrity distal to the injury site at the AC in the developing brain, where repeated injury exacerbates abnormalities, similar to adult TBI [16]. Such increases in FA, in view of the significantly reduced RD and unaltered AD, clearly report WM microstructural disruption and suggest potential myelin-based dysregulation of microstructural integrity, as RD is often associated with myelin changes whereas AD is associated with axonal injuries [35, 64].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in WM characteristics, such as myelin integrity [16, 37, 70], axonal responses [16, 70], and fiber organization [71], contribute to WM microstructure and likely alter DTI findings. Furthermore, the potential effects of the ongoing development of WM should not be overlooked [26].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations